Dinamika Hubungan Perusahaan dan Komunitas Konsumen: Sebuah Implikasi Stratejik bagi Pemasar - Hartono, Yudho (Universitas Prasetiya Mulya, 2008)
Nowadays we are facing a new phenomenon “suddenly emerged” consumer community in Indonesia. For a particular reason this emergence of community should be interesting because their existence give benefit to brand owners. It creates customers’ loyalty and commitment to the brand. Unfortunately, many brand owners are still not aware about the existence of consumer community. A new perspective is needed to bridge the gap between the brand owners and the community. To have a better relationship with the community, brand owners should understand the “face of community’s consumption”. This article describes activities that brand owners should do in developing such community. It is found that there is a dynamic of “test the water” relationship model between brand owners and the community. Brand owners should pay more attention to build a strong and long term relationship with the community as their strategy in order to gain sustainable benefit from this kind of relation.